Proposal for a Gamification Tour in Hrvatska Kostajnica – A Tribute to the Legend of Djed - Abalić, Ena; Bibković, Manuela; Grujić, Tena; Guta, Alina; Manc, Dora; Jeličić, Luka; Piljan, Ema; Vidas, Matteo; Roki, Lovre; Bešker, Rebeka; Juričić, Vedran; Veočić, Ines; et al. (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
In this paper, a concept for a gamified tour for the town of Hrvatska Kostajnica is proposed with the aim of enhancing the local tourism offer through a combination of culture, history and interactive elements. The tour is designed as an interactive game based on the local legend of Djed. It guides visitors through a series of tasks and challenges and connects them to the city's main attractions. Using a mobile application, participants explore landmarks such as the old town centre of Zrinski, the natural beauty of the Una River and places such as the Lenac family farm, promoting sustainable tourism and local agriculture. Gamification includes game elements such as points, rewards and leaderboards that increase engagement and create additional motivation to explore. The tour is adaptable to different age groups, ensuring broad accessibility and inclusiveness. This innovative approach helps to strengthen the tourist image of Hrvatska Kostajnica, extend the visitors' stay and foster an emotional connection to the destination. The gamified tour model is an innovative solution that can also help other smaller destinations to improve their offer, attract more tourists and preserve their cultural and natural heritage in a sustainable way.